Stereotyping and its manifestations in the theater of Eugene Ionesco (Al-Academy, 2024)
There is a class or group of people who share characteristics, methods, and methods of a type or style, even if they differ from each other in their divisions with these characteristics, that is, a template and model that defines certain images and things. The current research is divided into three chapters. The first chapter deals with the research problem, which is represented by the following question: “ What are the manifestations of stereotyping in the theater (Eugène Ionesco), then the importance of research and the need for it as it benefits scholars and workers in the field of theater, and then the goal of the research (learn about planning and its manifestations in the theater (Eugène Ionesco), and then the temporal limits of the period (1950-1955) And spatial (Romania) and objectivity, a study of stereotyping and its manifestations in the theater of Eugene Ionesco. The second chapter contained the theoretical framework and included three topics. The first topic was concerned with stereotyping conceptually, while the second topic was stereotyping socially. The third topic dealt with the features of stereotyping in the theatrical text. The third chapter was represented by research procedures and included society. The research included (8) theatrical texts, and then the research sample was chosen intentionally (the bald singer, the new tenant). The research relied on the descriptive approach in the analytical method, and the research concluded with the fourth chapter, including the results, conclusions, and a list of sources